A atuação do perito contador como auxiliar da justiça: uma perspectiva sobre a dissonância entre os agentes sob a ótica da geração e confirmação das expectativas. - Costa, Annelise Torres da (2024)
This study aims to understand the expectations and satisfactions of the various participants involved in the production and application of forensic accounting reports, essential tools in the resolution of judicial disputes. Forensic accounting, while respecting technical standards, aims to provide high-quality and impartial information, with the Accounting Information System as the main data source. The main objective of the research is to analyze the expectation of each participant in the process of preparing and analyzing the forensic report: the expert regarding the effort, performance, and rewards for the elaboration of a quality work; the lawyers who evaluate the result of the report, to accept it or, if pertinent, to challenge it; and the judge, who uses the report as a tool to aid in the verdict. Vroom's Expectancy Theory is applied to examine how the experts' expectations and motivation to produce high-quality work are linked to the desired rewards, such as fees, new appointments, and recognition. From the perspective of lawyers and judges, Oliver's Expectation Confirmation Theory is employed to understand whether expectations regarding the forensic accounting report are confirmed or not. Through interviews applied to experts, judges, and lawyers from the regions of the South, Southwest, Northeast, and Midwest, the study seeks to identify the expectations of these involved parties, the relationship between effort and performance in the production of quality reports, and how this can result in rewards for the expert. The study also aims to understand the perception of judges and lawyers regarding the confirmation of their expectations in relation to forensic reports. The uniqueness of the approach and the need for a better understanding of the motivations and expectations of those involved in the preparation and use of forensic accounting reports justify this research. The work has the potential to contribute to the practice of forensic accounting by identifying how the motivation of experts and the expectations of judges and lawyers can improve the quality of forensic reports and, consequently, the effectiveness of the judicial system. Moreover, the research contributes to the proposed line of studies - Managerial Accounting and Control in Organizations - facilitating future projects and the improvement of accounting practices.